A Case Report of Meigs’ Syndrome Caused by Ovarian Fibrothecoma with High Levels of CA125 - Yuan L; Cui L; Wang J; Gong L (International Journal of Women's Health, 2024)
Liqin Yuan, Lin Cui, Jie Wang, Li Gong Department of Gynecology, Rizhao People’s Hospital, Rizhao, Shandong Province, 276800, People’s Republic of ChinaCorrespondence: Li Gong, Rizhao People’s Hospital, Rizhao, Shandong Province, 276800, People’s Republic of China, Tel +86-18663351821, Email gongli0768@163.comPurpose: Meigs’ syndrome is a rare gynecological disease characterized by the triad of benign ovarian tumor, ascites, and pleural effusion. Ovarian malignancies should be highly suspected in a postmenopausal woman with a pelvic mass, ascites, hydrothorax, and an elevated carbohydrate antigen 125 (CA125) level. It can be challenging to make a preoperative diagnosis of Meigs’ syndrome. In this report, we present a case of Meigs’ syndrome caused by an ovarian fibrothecoma and review the relevant literature to raise awareness and avoid misdiagnosis.Case Presentation: An 82-year-old woman with a 2-week history of abdominal distension was admitted to the Department of Gynecology. Ultrasound and thoracoabdominal computed tomography scans showed a left-sided hypoechoic mass in the pelvic cavity with bilateral pleural effusion and massive ascites. The CA125 concentration was 1040 U/mL (normal, 0– 35 U/mL). With a working diagnosis of ovarian malignancy, the patient underwent ultrasound-guided fine-needle puncture of the pelvic mass and paracentesis to drain the ascites. The fine-needle puncture and paracentesis fluid analysis results revealed that the ascites did not contain any tumor cells, and the pelvic mass was identified as a spindle cell tumor. Immunohistochemistry confirmed that it was a sex-cord stromal tumor. Total abdominal hysterectomy and bilateral adnexectomy were performed under general anesthesia. The pathology results confirmed the mass to have been an ovarian fibrothecoma. At the 2-month postoperative follow-up, the ascites and hydrothorax had resolved and not recurred, and the CA125 level was normal.Conclusion: Despite the high suspicion of ovarian carcinoma in postmenopausal women presenting with pelvic mass, ascites, pleural effusion, and elevated CA125, Meigs’ syndrome should be considered.Keywords: Meigs’ syndrome, ascites, pleural effusion, CA125, ovarian fibrothecoma, ovarian cancer